(untitled) (Bangladesh Journal of Neuroscience, 2019)
Congenital myasthenic syndromes (CMS) comprise a heterogeneous group of rare inherited diseases in which the neuromuscular transmission in the motor plate is compromised by one or more genetic pathophysiological specific mechanisms are characterized by fatigable weakness of skeletal muscle (e.g., ocular, bulbar, limb muscles) with onset at or shortly after birth or in early childhood; rarely, symptoms may not manifest until later in childhood. The diagnosis of CMS is based on clinical findings, a decremental EMG response of the compound muscle action potential (CMAP) on low-frequency (2- 3 Hz) stimulation, absence of anti-acetylcholine receptor (AChR) and anti-MuSK antibodies in the serum, a positive response to acetylcholinesterase (AchE) inhibitors and lack of improvement of clinical symptoms with immunosuppressive therapy. Pathogenic variants in one of multiple genes encoding proteins expressed at the neuromuscular junction are currently known to be associated with subtypes of CMS. The most commonly associated genes include: CHAT, CHRNE, COLQ, DOK7, GFPT1 and RAPSN. We studied on a sibling presented with progressive fatigability and fluctuating ptosis with frequent exacerbations of muscle weakness during infections since infancy. On both cases CT scan of chest were negative for thymoma, antibodies against the acetylcholine receptor (AChR) and the muscle specific kinase (MuSK) were negative and decremental response on electrophysiological study of Repetitive nerve stimulation (RNS) and EMG were consistent with disease of neuromuscular junction (post synaptic) and they were only on pyridostigmine for long time with marked improvement of symptoms and signs. Considering all scenario both of our cases mostly fits with the autosomal recessive, post synaptic CMS associated with Rapsyn deficiency. Objective : As in Bangladesh, there is inadequate data on the epidemiological profile of CMS, our aim is to describe these cases for their rarity and the difficulty encountered in diagnosis as they are easily confused with Juvenile Myasthenia Gravis (JMG) and familial myopathies. As both the cases are very rare, it should be an original article. Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 95-103